Richard Rorty : His Philosophy Under Discussion. - Vieth, Andreas (Münstersche Vorlesungen zur Philosophie (Series), 2005)
Without doubt Richard Rorty is one of the most honored, famous and disputed philosophers of our days. All over the world interest in his inspiring and provoking thoughts goes beyond the circles of academic philosophy. The present volume includes ""The Brain as Hardware, Culture as Software"" and ""Philosophy-Envy"" of Richard Rorty, papers presented by students of the philosophy department at university of Münster and Rorty's responses to and comments on them. Rorty's lecture has been publicly presented at the 8. Münstersche Vorlesungen zur Philosophie on may 26th 2004. The students presented.